Does exercising with a face mask affect athletes performance? - Attar, W. S. A. A.; Husain, M. A. (British Journal of Sports Medicine, 2021)
Background: With the spread of Coronavirus Disease (COVID-19) , wearing a mask became mandatory publicly and during exercise. Objective: To investigated the prevalence of wearing face masks and their impact on athletes` comfort and performance. Design: A cross-sectional study. Setting: An online survey. Patients (or Participants) A total of 633 athletes participated in the study. Interventions (or Assessment of Risk Factors): A self-administered web-based questionnaire was developed. Primary data were correlated with secondary data such as average temperatures, which were obtained from open sources. Main Outcome Measurements: The primary outcomes were the prevalence of wearing face masks and their impact on athletes` comfort and performance. Results: A total of 633 athletes from 188 countries participated in the study in the period between June and July 2020. They were mostly males (n = 536) and aged 20-29 years (n = 290). A total of 633 athletes completed a self-administered web-based questionnaire. They were mostly males (n = 536) and aged between 20-29 years old (n = 290). Four hundred twenty-three athletes reported that their performance was affected due to wearing a mask. Using a mask while exercising significantly affected performance, X 2 2 = 633, p <.001. The type of mask worn also significantly impacted performance, X 2 6 = 656.5, p <.001. Further analysis showed that 100% of those wearing N95, FFP2, or the equivalent mask reported affected performance compared to 90.9% for athletes wearing surgical masks. The point-biserial correlation was negative between performance and maximum ambient temperature, r pb = -.435, p <.001). Conclusions: Performing high-intensity exercises while wearing face masks may lead to discomfort, breathing restrictions, and impaired fitness level of athletes. It is recommended to review the healthcare policies of wearing masks while exercising.